On the Distance Dependence of the Price Elasticity of Telecommunications Demand; Meta-analysis, and Alternative Theoretical Backgrounds - Hans Ouwersloot; Piet Rietveld (Tinbergen Institute, 1997)
The positive correlation between the absolute price elasticity of telecommunications demand and the distance of the calling relation is well known. In this paper we first present a meta-analysis of existing studies to buttress the distance dependence empirically. The analysis confirms the existence of distance dependence, and gives insight into the size of the effect.Next we look for various explanations of the distance dependence. We analyse the roles of the functional form of demand functions in conjunction with the dependence of price on distance, and consider whether spatial interaction theory can provide an explanation. One of the interesting findings isthat the price effect may explain the distance dependence, but that this explanation is not unequivocal. On the other hand we show that incorporating spatial interaction theory elements in a quite basic utility maximization model of information demand also leads to distance dependent telecommunicationsdemand (keeping prices of calling fixed).
Keywords: 330; Telekommunikation; Mikroökonomische Konsumfunktion; Preiselastizität; Räumliche Interaktion; Theorie; Welt